Analisis Biaya dan Waktu Pekerjaan Finishing dengan Metode Earned Value di Proyek Gedung Serba Guna Kabupaten Gresik - Wahyudi, Muhammad; Oetomo, Wateno; Mudjanarko, Sri Wiwoho (Jurnal Spesialis Teknik Sipil (JSpTS), 2025)
Architectural work in a construction project, generally is a non-structural work. However, the implementation can require a long time and a large cost weight. The implementation of finishing work in multi-purpose building construction project of Gresik Regency that was already running and had problems, that is a lot of workers but lack of work progress, so an increase of the cost from budget planned. Therefore it needs to doing research that for get the actual time of project implementation and get Estimate at Completion (EAC). The results is that the actual time of project implementation is not suitable with time of project planning. The project has been to late so there is a decrease in project performance. In the 1st week of project implementation on time, in the 2nd week until the 15th week the project has been to late (schedule overrun). So based on the time of implementation, the project has decreased performance. The total estimated cost can be seen from the Estimate at Completion (EAC) calculation, which is Rp.274,424,152.89.